Advances in accounting education : teaching and curriculum innovations. Volume 24 - Calderon, Thomas G. (Bingley, U.K. : Emerald Publishing Limited, 2020)
Advances in Accounting Education(AAE) is a high-quality publication of both empirical and non-empirical research that investigates vital matters within teaching, learning, and curriculum development. By focusing on these topics, it works to support the improvement of accounting programs at colleges and universities, as well as foster innovative discussion and significant contributions to faculty development. This 24th volume features 11 peer-reviewed papers surrounding five key themes: (1) research on student attitudes and behavior, (2) cases and pedagogical approaches in tax, (3) financial reporting and introductory accounting, (4) research about the CPA exam, and (5) international perspectives. It considers a variety of topics within these themes, from student study choices and changes in ethical attitudes over time to policy implications for the accounting profession. It even includes an instructional case for use in intermediate accounting courses and a comprehensive pedagogical approach (with a case) for teaching a complex topic in taxation. With international and nuanced perspectives from expert voices in the field, AAE is essential reading for students and accounting educators. Some practitioners and regulators in the accounting profession may also find useful policy-related nuggets in Volume 24.
THEME 1: RESEARCH ON STUDENT ATTITUDES AND BEHAVIORChapter 1: Study Choices by Introductory Accounting Students: Those Who Study More Do Better and Text Readers Outperform Video Watchers; Earl K. Stice, James D. Stice and Conan Albrecht -- Chapter 2: Decade Comparisons: Do Students' Ethical Attitudes Shift? Christine Cheng, Renee Flasher and Kristy Schenck THEME 2: CASES AND PEDAGOGICAL APPROACHES IN TAX -- Chapter 3: Meeting the Demands of the Accounting Curriculum: An Integrated Approach using a Tax Research Case Assignment; Mollie T. Adams, Kerry K. Inger and Michele D. Meckfessel -- Chapter 4: Bonus Depreciation and its Effect on Net Present Value in Relation to Capital Purchases; Kristy Schenck, Frances A. Stott and Aaron B. Wilson -- Chapter 5: Evaluating the Impact of the VITA Program on Attitudes and Motives Regarding Volunteering and Civic Engagement; Rafael Efrat and Scott W. Plunkett THEME 3: FINANCIAL REPORTING AND INTRODUCTORY ACCOUNTING -- Chapter 6: An Instructional Case: Making the Case for Unlimited Vacation Days at Altech; Deirdre M. Collier and Hannah Rozen -- Chapter 7: The Importance of Supplemental Resources in Accounting Education; Robert O'Haver THEME 4: RESEARCH ABOUT THE CPA EXAM -- Chapter 8: Accounting Faculty and Professional Certifications: Experiences and Perceptions; Jason Bergner, Yining Chen and Melloney Simerly -- Chapter 9: A Closer Look at Research on CPA Exam Success; Thomas Calderon and Albert Nagy THEME 5: INTERNATIONAL -- Chapter 10: Is the Pause Method in Teaching Auditing Applicable in a Different Educational Environment: A Replication Study; Theodore T. Y. Chen, Hui Fang, Yanling Wang and Qiang Zhou -- Chapter 11: Introducing Computer-Marked Tests in an Online Financial Accounting Course: Patterns in Academic Performance and Approaches to Assessment Design; Ruslan Ramanau, Jane Hughes and Paul Grayson.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Accounting -- Study and teaching (Higher); Educational innovations; Business & Economics -- Accounting -- General; Accounting